(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
All fourteen isolates of Pencillium expansum were screened for the production of L-glutaminase. The screening of L-glutaminase producing isolates carried out by using modified Czapek Dox’s agar plate. Out of fourteen isolates the strain P. expansum KGSSD 08 were showed high and potential L-glutaminase producer. It showed maximum 1.11cm zone of diameter. Then the rapid confirmation of L-glutaminase producing Pencillium expansum KGSSD 08 were carried out by thin layer chromatography and the Rf Values were determined. The Rf value is 0.268.This Rf was close to that of standard glutamic acid.